Book Review. Fermor, Our Companion: Dan Horațiu Popescu’s Layers of the Text & Context. Patrick Leigh Fermor & Friends (Papers in Arts and Humanities, 2022)
Sir Patrick Leigh Fermor (1915-2011) is the writer who managed to turn travelogues into a genre deserving to be called an art form. The contrast between Fermor's travelogue and the new configurations and shapes undertaken by travel writing nowadays becomes comforting through the intrinsic qualities of his écriture: the transformative encounters with known and unknown people, the preference for the adventurous less travelled paths (even on foot) of Central and Eastern Europe before WWII (1933-1939), the assessment of historical events through his own feelings and personal history. Fermor raised the stakes by making his real and reflective voyages grow into the very matter of literature (rather than be a mere setting or an annex of it) because of his erudition and because of his genuine capacity to create authentic connections between himself and the people he met, between past and present, between inter-war years and the post-WWII world, between Western and Eastern cultures in the cold-war era.
Keywords: Fermor; travelogue; Central Europe; Eastern Europe